Glial M6B stabilizes the axonal membrane at peripheral nodes of Ranvier. Issue 4 (28th December 2017) - Bang, Marie L; Vainshtein, Anya; Yang, Hyun‐Jeong; Eshed‐Eisenbach, Yael; Devaux, Jerome; Werner, Hauke B; Peles, Elior
Abstract: Glycoprotein M6B and the closely related proteolipid protein regulate oligodendrocyte myelination in the central nervous system, but their role in the peripheral nervous system is less clear. Here we report that M6B is located at nodes of Ranvier in peripheral nerves where it stabilizes the nodal axolemma. We show that M6B is co‐localized and associates with gliomedin at Schwann cell microvilli that are attached to the nodes. Developmental analysis of sciatic nerves, as well as of myelinating Schwann cells/dorsal root ganglion neurons cultures, revealed that M6B is already present at heminodes, which are considered the precursors of mature nodes of Ranvier. However, in contrast to gliomedin, which accumulates at heminodes with or prior to Na + channels, we often detected Na + channel clusters at heminodes without any associated M6B, indicating that it is not required for initial channel clustering. Consistently, nodal cell adhesion molecules (NF186, NrCAM), ion channels (Nav1.2 and Kv7.2), cytoskeletal proteins (AnkG and βIV spectrin), and microvilli components (pERM, syndecan3, gliomedin), are all present at both heminodes and mature nodes of Ranvier in Gpm6b null mice. Using transmission electron microscopy, we show that the absence of M6B results in progressive appearance of nodal protrusions of the nodal axolemma, that are often accompanied by the presence of enlarged mitochondria. Our results reveal that M6B is a Schwann cell microvilli component that preserves the structural integrity of peripheral nodes of Ranvier. Main Points: M6B as a new glial component of the nodes of Ranvier. M6B is co‐localized and associates with gliomedin at Schwann cell microvilli. Absence of M6B leads to morphological abnormalities of the nodal axolemma.